Task analysis provides data for MRI curriculum planning. - Grey ML; Jensen SC (Radiologic Technology)
No standardized education or training program currently exists for magnetic resonance imaging technology. The results of this initial national task analysis will assist in development of a curriculum guide and serve as a baseline for further research.